(untitled) (African Journal of Biomedical Research, 2024)
Aging is associated with progressive decline in functions which may impact cardiovascular health negatively. This cross-sectional study assessed anthropometric indices, blood pressure and some apolipoproteins in older adults in Nnewi. One hundred and twenty-eight participants (64 older adults and 64 control subjects) were recruited for the study using simple random sampling. Body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-hip ratio (WHR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were determined using standard methods. Five milliliters (5ml) of venous sample were taken from each participant after 10–12 hours of fasting, minimizing stasis, and placed in plain containers for the determination of apolipoprotein A–I (apoA–I) and apolipoprotein B100 (apoB100) levels using Immnoturbidimetric method. The older persons had significantly (p<0.05) lower mean serum apoA-I and higher apoB100 level, apoA-I/apoB100 ratio, BMI, WHR, SBP and DBP values compared to control subjects respectively. Furthermore, the mean serum apoB100 and apoB100/apoA-I ratio, as well as the mean WC, WHR, SBP, and DBP, were all significantly higher while the mean serum apoA-I level was lower in the older males compared to the control males (p<0.05). Also the older females had significantly higher mean SBP, DBP, apoB100 and apoB100/apoA-I ratio with significantly lower apoA-I compared to the female control (p<0.05). The findings of this study reveal considerable changes in anthropometric measurements, blood pressure, and apolipoprotein levels in older persons, necessitating guidance for Medical Laboratory scientists and Clinicians in their interpretations.